Effect of stocking density on broiler performance and carcass characteristics - Amgawer, Hussien; Salem, Naji A.; Alshelmani, Mohamed I. (Journal of Pure & Applied Sciences, 2023)
The current study was conducted in the eastern suburbs of Benghazi (Tocra) from 17 May 2121 to 7 July 2021 to evaluate the effect of stocking density on broiler performance and carcass characteristics. A total of 120 one-day-old unsexed chicks (Ross 308) were raised on a closed house system. The chicks were reared on a floor system containing pens having 1m2 useful areas. On day 21, the birds were randomly distributed into three treatments (stocking densities) represented as 5 birds/m2, 8 birds/m2 and 11 birds/m2 on the 1st, 2nd and 3rd treatments, respectively with five replicates in each. The birds were fed by starter and grower diets containing 22% and 20% crude protein, respectively. The initial body weight, body weight gain (BWG), feed intake, feed conversion ratio (FCR), carcass, legs, drumsticks, breast yields and internal organs were calculated. The results showed significant differences (P0.05) were shown in FCR among the treatments. no significant differences (P>0.05) were found in carcass characteristics or the internal organs (gizzard, heart, liver). As can be seen, better growth performance was observed in the group of broilers with low stocking density compared to the two other groups, although more research is needed regarding the stocking density of poultry.